2014
DOI: 10.1161/circep.113.000806
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Catheter Ablation Versus Medical Treatment of Atrial Fibrillation in Heart Failure (The CAMTAF Trial)

Abstract: Background-Restoring sinus rhythm in patients with heart failure (HF) and atrial fibrillation (AF) may improve left ventricular (LV) function and HF symptoms. We sought to compare the effect of a catheter ablation strategy with that of a medical rate control strategy in patients with persistent AF and HF. Methods and Results-Patients with persistent AF, symptomatic HF, and LV ejection fraction <50% were randomized to catheter ablation or medical rate control. The primary end-point was the difference between gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
382
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(417 citation statements)
references
References 49 publications
(61 reference statements)
13
382
1
7
Order By: Relevance
“…At the same time, the data illustrate that CA may significantly improve cardiac function in patients with HF and AF, which corroborates the conclusions of previously published studies (15)(16)(17). Furthermore, the present study has revealed that hs-CRP, duration of AF and LAD are independent predictors of higher recurrence rates of AF in patients with HF.…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, the data illustrate that CA may significantly improve cardiac function in patients with HF and AF, which corroborates the conclusions of previously published studies (15)(16)(17). Furthermore, the present study has revealed that hs-CRP, duration of AF and LAD are independent predictors of higher recurrence rates of AF in patients with HF.…”
Section: Discussionsupporting
confidence: 92%
“…The results from this early study also contrast with more recent findings from the Catheter Ablation Versus Medical Rate Control for Atrial Fibrillation in Patients With Heart Failure (ARC-HF) and Catheter Ablation Versus Medical Treatment of Atrial Fibrillation in Heart Failure (CAMTAF) trials, which both showed significant improvement in exercise capacity and QoL with AF ablation in comparison with pharmacological rate control. 14,36 The CAMTAF trial also showed a significant improvement of LVEF after 6 months of follow-up with AF ablation in comparison with pharmacological rate control (+8.1 [95% CI, 3.0-13.1] versus -3 [95% CI, -7.7 to 0.5]; P<0.001). 36 Similarly, the ARC-HF trial reported a trend toward a higher LVEF improvement with AF ablation (mean difference, +5.6% (95% CI, −0.1 to +11.3; P=0.055) after 12 months of follow-up.…”
Section: Circulationmentioning
confidence: 96%
“…113,433 Numerous studies have evaluated the efficacy of catheter ablation of both paroxysmal and persistent atrial fibrillation with significant impairment of systolic function. 437,[466][467][468][469][470][471][472][473] The weight of evidence is that sinus rhythm can be successfully achieved in 50 -80% of patients although repeat procedures are common and follow-up periods are usually not more than 12 months. Successful ablation has been associated with significant improvements in ejection fraction and reduction in atrial size in the majority of studies.…”
Section: Age and Atrial Fibrillation Ablationmentioning
confidence: 99%